Human-Centered Design of a Clinical Decision Support for Anemia Screening in Children with Inflammatory Bowel Disease - Miller, Steven D.; Murphy, Zachary; Gray, Joshua H.; Marsteller, Jill; Oliva-Hemker, Maria; Maslen, Andrew; Lehmann, Harold P.; Nagy, Paul; Hutfless, Susan; Gurses, Ayse P. (Applied Clinical Informatics, 2023)
Background Inflammatory bowel disease (IBD) commonly leads to iron deficiency anemia (IDA). Rates of screening and treatment of IDA are often low. A clinical decision support system (CDSS) embedded in an electronic health record could improve adherence to evidence-based care. Rates of CDSS adoption are often low due to poor usability and fit with work processes. One solution is to use human-centered design (HCD), which designs CDSS based on identified user needs and context of use and evaluates prototypes for usefulness and usability.Objectives this study aimed to use HCD to design a CDSS tool called the IBD Anemia Diagnosis Tool, IADx.Methods Interviews with IBD practitioners informed creation of a process map of anemia care that was used by an interdisciplinary team that used HCD principles to create a prototype CDSS. The prototype was iteratively tested with “Think Aloud” usability evaluation with clinicians as well as semi-structured interviews, a survey, and observations. Feedback was coded and informed redesign.Results Process mapping showed that IADx should function at in-person encounters and asynchronous laboratory review. Clinicians desired full automation of clinical information acquisition such as laboratory trends and analysis such as calculation of iron deficit, less automation of clinical decision selection such as laboratory ordering, and no automation of action implementation such as signing medication orders. Providers preferred an interruptive alert over a noninterruptive reminder.Conclusion Providers preferred an interruptive alert, perhaps due to the low likelihood of noticing a noninterruptive advisory. High levels of desire for automation of information acquisition and analysis with less automation of decision selection and action may be generalizable to other CDSSs designed for chronic disease management. This underlines the ways in which CDSSs have the potential to augment rather than replace provider cognitive work.
Keywords: clinical decision support systems; usability testing; human-centered decision; clinical workflows